NAPHTHALENE MOTHBALLS POISONING LEADING TO METHEMOGLOBINEMIA IN A YOUNG CHILD (Journal of Forensic Medicine & Toxicology, 2022)
Mothballs contain Naphthalene, a potent aromatic hydrocarbon, and are commonly used in Indian households as a deodorizer and moth repellent. It is widely available in all grocery shops, street shops, and supermarkets. The lethal dose of acute naphthalene toxicity is 5–15 g for adults and 2–3 g for children.1 One mothball may contain 0.5-5 g of naphthalene depending upon its size. Naphthalene poisoning has been reported in children who accidentally suck or chew even one mothball because of its candy-like appearance.2 Toxic effects had been reported through various modes of exposure, including ingestion, inhalation, or external skin contact.3 Its toxic manifestations are mainly due to the production of oxygen free radicals leading to lipid peroxidation, deoxyribonucleic acid (DNA) damage, and red cell membrane damage leading to intravascular hemolysis. It converts hemoglobin to methemoglobin due to its potent oxidizing property.4 In mothball preparation,naphthalene has been replaced with the less toxic substance 1,4-dichlorobenzene in many countries. But in India, naphthalene containing mothballs are still available and they are poorly labeled.5 Very few cases of naphthalene poisoning in children are being reported and the actual toll due to accidental ingestion of this commonly available household substance may be too high.4 We report a case of accidental naphthalene poisoning in a one year seven months old female child who presented with methemoglobinemia. The Institutional Ethics Committee has approved presentation/publication of this case report.
Keywords: naphthalene; deoxyribonucleic; deodorizer